Personal learning environments: Integration of Web 2.0 applications and content management systems - Oliveira, Lino (2018)
The use of Web 2.0 applications in learning and teaching (L&T) has intensified in recent years, more driven by teachers and students than by educational institutions strategy. This paper presents an ongoing project that implements a platform for creating personal learning environments controlled by students, integrating Web 2.0 applications and content management systems. The platform will enable the safe use of content created in Web 2.0 applications in the evaluation process, allowing its publication in the infrastructure controlled by the Higher Education Institution, thus contributing to the adequacy of the binomial teaching / learning process involved in the new paradigm Bologna.